SISTEM PENGOBATAN DAN PERSEPSI MASYARAKAT TERHADAP PENGOBATAN TRADISIONAL BERDUKUN ATAU BULIAN DI DESA SUNGAI PASIR PUTIH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Sami Rafles Handika; Defri Yoza; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Talang Mamak is a tribal society in Indragiri Hulu district, spread over 9 districts in Indragiri Hulu regency. Talang Mamak tribe settlements are mostly located on the edge of the forest, the forest and the edge of the rive flow Indragiri Hulu. Berdukun or bulian is a traditional healing rituals Talang Mamak community by asking the user to supernatural beings as well as using traditional tools and materials whose activities led by a Shaman or Kumantan and auxiliary rituals such as Bujang Bayu, Complementary Old and Dendi. The purpose of this research is to determine the treatment system and the public perception Sungai Pasir Putih subdistrict Kelayang to traditional treatments berdukun or bulian. The method in this research is the method Snownball Sampling. Results showed that the system of public confidence in the Talang Mamak cure various diseases by way of treatment to traditional healers known as traditional medicine berdukun or bulian and subdistrict public perception Kelayang to traditional treatments berdukun or bulian very good perception.Keywords: Traditional Medicine, Talang Mamak, Berdukun or Bulian